The Relationship of Group Research and Current Practices in Group Counselling and Therapy in Metro Toronto - Wolfgang, Aaron; Pierson, Donald (Canadian Journal of Counselling and Psychotherapy, 2012)
One hundred and sixty-five practicing group leaders in the Metropolitan Toronto area were interviewed using a questionnaire designed to explore the correspondence between current group counselling and what the research literature suggests. Responses were discussed under four headings: 1) pretherapy considerations, 2) group leader orientation, 3) outcome evaluation and, 4) size and open/closed issues. Group leaders were found to be aware of and concerned with many issues of current concern to researchers and theoreticians. All of the group leaders were able to specify goals for change and report methods of evaluating outcome although there was an excessive reliance on subjective instruments (verbal andwritten self-reports). Seventy-five per cent of the group leaders reported that theresearch literature had minimal relevance or no relevance to clinical practice. Some current findings from the research on group practices are discussed.